Weeds of Paddy Field at Kirtipur, Kathmandu - Manandhar, Sailaza; Shrestha, Bharat B; Lekhak, Hari D (Scientific World, 2010)
Paddy (Oryza sativa L. var. Taiching-127) fields of Kirtipur, central Nepal, were studied to evaluate the effects of weeds on crop yield during June to October 2003. Weed community was recorded in permanently marked plots (2 x 2 m2 each), and grain and straw yields were measured. The effect of aqueous extracts (2 to 10%) of leaf, stem and root of dominant weeds (Echinochloa colona, E. crusgalli, Cyperus iria and Ageratum conyzoides) on germination and seedling growth of the paddy (Taiching-127) was examined in the laboratory. Altogether 52 weed species (27 dicot and 25 monocot) belonging to 32 genera and 15 families infested the paddy. The maximum weed density was observed in September (105 pl/m2). There was significant reduction in straw and grain yield of paddy in weedy plots and negative correlation between weed species richness and straw yield. Crop weed competition reduced straw yield by 13% to 38% and grain yield by 25% to 47%. Weed growth changed pH and reduced soil nitrogen and phosphorus content. Aqueous extracts of root, stem and leaf of dominant weeds (Echinochloa colona, E. crus-galli, Cyperus iria and Ageratum conyzoides) showed a weak effect on seeds germination however most of them had inhibitory effect on root and shoot elongation of paddy seedlings. Root elongation was more sensitive to allelopathic inhibition than shoot elongation. Stem extract of these weeds showed higher inhibition on seedling growth of paddy than leaf and root extract except in Ageratum conyzoides in which root extract showed highest inhibition. Keywords: Allelopathy; Crop-weed competition; Soil nutrients; Germination; Grain yield. DOI: 10.3126/sw.v5i5.2665 Scientific World, Vol. 5, No. 5, July 2007 100-106